Effect of Salinity and Nitrogen on Heavy Metal Tolerance and Accumulation Potential in Rumex maritimus - Lāsma Neiceniece; Astra Jēkabsone; Una Andersone-Ozola; Lidia Banaszczyk; Andis Karlsons; Anita Osvalde; Gederts Ievinsh (Stresses, 2025)
The aim of the present study was to assess heavy metal tolerance and its accumulation potential in coastal nitrophilic species Rumex maritimus, and to study the possible effects of nitrogen fertilizer and salinity on the characteristics of metal-treated plants. Two experiments were performed in partially controlled greenhouse conditions: (1) gradual treatment with increasing concentrations of Cd, Pb, Cu, Mn, and Zn; and (2) acute treatment with Cd, Pb, and Cu on the background of different nitrogen fertilizer amendment rates (0.15 and 0.30 g L−1 N) and salinity (50 and 100 mM). R. maritimus plants were extremely tolerant to treatment with all metals, with no negative effect on total leaf biomass both in the case of gradual or acute treatment. However, the number and biomass of dry leaves increased under high doses of heavy metals, and the effect was more pronounced in the case of acute treatment. All studied metals were excluded from the roots and young leaves, predominantly accumulating in the dry leaves, reaching 250 mg kg−1 for Cd, 2000 mg kg−1 for Pb, and 500 mg kg−1 for Cu. In the second experiment, the presence of increased nitrogen in the substrate positively affected the growth of R. maritimus plants and their morphological response to heavy metals, but salinity affected metal accumulation. Photosynthesis-related parameters, leaf chlorophyll concentration, and the chlorophyll a fluorescence parameter Performance Index Total confirmed that heavy metals had no negative effect on the physiological state of photosynthetically active leaves. It is concluded that R. maritimus plants have exceptional potential for practical phytoremediation needs due to the high tolerance and accumulation potential for heavy metals.